Heterogeneity Characteristics of Lacustrine Shale Oil Reservoir Under the Control of Lithofacies: A Case Study of the Dongyuemiao Member of Jurassic Ziliujing Formation, Sichuan Basin - Peng Li; Peng Li; Zhongbao Liu; Haikuan Nie; Haikuan Nie; Xinping Liang; Xinping Liang; Xinping Liang; Qianwen Li; Pengwei Wang (Frontiers in Earth Science, 2021)
The lacustrine shale in the Dongyuemiao Member of the Fuling area, Sichuan Basin, is widely distributed and has huge shale oil resource potential. It is one of the important replacement areas for shale oil exploration in China. To investigate the key shale oil evaluation well, Well FY10, in the Fuling area, X-ray diffraction (XRD) mineral analysis, Rock-Eval, argon ion polishing-scanning electron microscope (SEM), Mercury injection capillary pressure (MICP), and low pressure nitrogen adsorption were launched to determine the heterogeneity of the pore system in the lacustrine shale of the Dongyuemiao Member. The mineral composition exhibits a high degree of heterogeneity, and the shale can be divided into two main lithofacies: argillaceous shale and mixed shale. The porosity ranges from 2.95 to 8.43%, and the permeability ranges from 0.05 to 1.07 × 10−3 μm2. The physical properties of mixed shale are obviously better than those of argillaceous shale. Inorganic mineral pores, such as linear pores between clay minerals and calcite dissolution pores, are mainly developed, while a small amount of organic pores can be observed. The average total pore volume (Vp) is 0.038 ml/g with an average specific surface area of 5.38 m2/g. Mesopores provide the main Vp (average 61.72%), and micropores provide mostly specific surface area. TOC imposes a strong controlling effect on the development of micropores. Clay minerals are the main contributors to mesopores and macropores. The organic-inorganic interaction during the process of diagenesis and hydrocarbon generation controls the formation of shale pore systems.